Tamoxifen induces ultrastructural alterations in membranes of Bacillus Stearothermophilus - Luxo, C. (2003)
Tamoxifen (TAM), a non-steroid antiestrogen, is the mostly used drug for chemotherapy and chemoprevention of breast cancer. However, the mechanisms by which TAM inhibits cell proliferation in breast cancer are not fully understood. TAM strongly incorporates in biomembranes and a variety of effects have been assigned to biophysical and biochemical interactions with membranes. Therefore, a better understanding of the physicochemical basis of interaction of TAM with biomembranes is essential to elucidate the molecular mechanisms of action. A strain of Bacillus stearothermophilus has been used as a model to clarify the interaction of TAM with the cell membrane. TAM effects on the ultrastructure of membranes of this bacterium were evaluated by electron microscopy. Important ultrastructural alterations were observed in B. stearothermophilus treated with TAM, namely change in the geometry of the membrane profile from asymmetric to symmetric, disaggregation of ribosomes, coagulation of the cytoplasmic matrix, occurrence of mesossomes, appearance of fractures in membranes and the alteration of the ultrastructure of cell wall. These ultrastructural alterations confirm that TAM is a membrane-active drug and that membrane damage may be involved in molecular mechanisms of cell death induced by this drug.